Disease in one lactation is associated with a greater incidence of the same disease in the subsequent lactation in dairy cows - Duarte Ruiz Diaz, Santiago Enrique (Kansas State University, 2024)
Objectives were to evaluate if having a disease in one lactation is associated with the risk of developing the same disease in the subsequent lactation and to identify risk factors for prevalent postpartum diseases. A total of 13,761 cow-lactations from 6,179 Holstein cows from two dairy farms located in Central California and two dairy farms located in North Florida were used in this retrospective study. Data were retrieved from farm management software from 2007 to 2013 and included prevalent postpartum disorders, such as dystocia, stillbirth, retained placenta, metritis, clinical hypocalcemia, hyperketonemia, displaced abomasum, and mastitis. Data were analyzed by logistic regression with the GLIMMIX procedure of SAS and included the fixed effects of history of the disease, parity, the interaction between the history of disease and parity, and the random effect of farm. Having dystocia increased the risk (odds ratio [OR] = 1.48; P < 0.001) of having dystocia in the subsequent lactation (25.5 vs. 18.8%). Having a stillbirth tended to increase the risk (OR = 1.58; P = 0.07) of having a stillbirth in the subsequent lactation (5.0 vs. 3.3%). Having retained placenta increased the risk (OR = 1.63; P = 0.002) of having retained placenta in the subsequent lactation (9.5 vs. 6.0%). Having metritis increased the risk (OR = 1.68; P < 0.001) of having metritis in the subsequent lactation (19.0 vs. 12.2%). Having clinical hypocalcemia increased the risk (OR = 13.32; P < 0.001) of having clinical hypocalcemia in the subsequent lactation (19.7 vs. 1.8%). Having hyperketonemia increased the risk (OR = 1.91; P < 0.001) of having hyperketonemia in the subsequent lactation (32.5 vs. 20.2%). Having displaced abomasum increased the risk (OR = 3.68; P = 0.02) of having displaced abomasum in the subsequent lactation (1.35 vs. 0.37%). Having mastitis increased the risk (OR = 2.10; P < 0.001) of having mastitis in the subsequent lactation (16.8 vs. 8.8%). For all the variables analyzed, the interaction between disease history and parity was not significant. Our data indicate that cows with a history of the disease or disorder are more likely to develop the same condition, suggesting a genetic component in the pathogenesis of postpartum diseases and disorders. In addition, our data suggests that the adaptive immune response to infectious diseases such as metritis and mastitis may not last until a subsequent lactation or may be insufficient to reduce the risk of diseases.
Keywords: Postpartum diseases; Dairy cows; Uterine diseases; Metabolic conditions; Transition period; Risk of recurrence